Cellular and molecular aspects of degenerative disc disease and potential strategies of biological therapy - A. V. Novikova; N. G. Pravdyuk; N. A. Shostak (Klinicist)
Back pain is one of the main global health problems with a high level of prevalence and patients’ disability. In most cases, it is associated with degenerative spine damage (degenerative disc disease), dorsopathy, discopathy (M51 and M53 according to the International Classification of Diseases, 10th revision), affecting all levels of the intervertebral disc (IVD) (cytological, chemical and biochemical) as a whole as well as biological molecules that regulate homeostasis of the disc intercellular substance (growth factors, pro-inflammatory cytokines, enzymes). A key point in IVD dehydration is that catabolic processes predominate over anabolic ones due to changed gene expression in the corresponding biologically active molecules, disc angiogenesis and neoinnervation of the structures of the fibrous ring and pulpous nucleus. The latter is responsible for chronic pain in patients.Cells supporting homeostasis in nucleus pulpous, chondrocytes, continuously synthesize and restore proteoglycans and hyaluronic acid in nucleus pulpous, restoring shock-absorbing functions of the vertebral-motor segment. Decreased activity and death of chondrocytes in the avascular disc structure is a serious problem for reparative medicine. In accordance with IVD molecular-cellular mechanisms, numerous approaches to treat degenerative disc disease are being developed, each of which, influencing one of the links in the pathogenesis, has a direct or indirect effect on IVD repair.The article describes morphology, pathogenesis and genetics of degenerative disc disease, as well as main modern strategies of biological therapy: tissue engineering, biologically active substances locally used in IVD matrix, including PRP therapy (Platelet Rich Plasma therapy), methods of gene (using the viral vector) and cell therapy, as well as experience in the local use of genetically engineered biological products. Most successful studies are a combination of cell and gene therapy with the use of synthesized matrices.